Penguatan Nasionalisme Millenial Dalam Politik : Studi Kasus Kader Sekolah Penggerak Partisipatif Badan Pengawas Pemilu Republik Indonesia - Inggar Saputra; Firdaus , Firdaus (Universitas Terbuka, 2023)
Abstract: As the year 2024 approaches, which is often referred to as the political year, the atmosphere of Indonesian politics is believed to be heating up. Hate speech, fake news hate speech, fake news, identity politics and money politics are threats in giving birth to elections with integrity. To achieve victory, politicians have the potential to utilize all means to win voters, including young or millennial voters. Generation Millennials are the generation born between 1980 and 2000. They are characterized as creative, connected to social media and have high self-confidence. high self- confidence. If the destructive potential of political battles hit their unstable emotional maturity, it will certainly have a negative impact on the neglect of morality, ethics and to the neglect of morality, ethics and the value of civility in millennial life. For this reason, participatory activist school cadres are needed to strengthen nationalism and form millennials. strengthen nationalism and form smart, critical and active millennials in facing political turbulence in the era of political in facing political turbulence in the post truth era in the 2024 elections in the 2024 election. This research uses a qualitative descriptive research method descriptive qualitative research method. Data collection techniques using literature studies, observation, in-depth interviews and documentation. The result of the research explained how the participatory activist cadre school was able to provide participants with an understanding of the situation of democracy, national politics national politics and how to strengthen nationalism that is appropriate in facing the developing political conditions. Strengthening nationalism especially in terms of character education through the values of morality, ethics and political civility, both physical actions and the use of both physical actions and utilization of social media in supporting this. Social media utilization in supporting this. The conclusion of the research is participatory activist cadre schools can form a basic understanding of supervision and preventive action against potential destructive threats in the 2024 elections.